Monks, money, and morality: the balancing act of contemporary Buddhism - Brumann, Christoph; Abrahms-Kavunenko, Saskia; Świtek, Beata (Bloomsbury Academic, 2021)
"This book dispels popular understandings of Buddhism as a religion that emphasizes the renunciation of worldly goods, by examining how Buddhist temples and the monastic community (the sangha) require tangible resources in order to sustain themselves. The first book to focus on the material and financial relations of contemporary Buddhist monks, nuns, temples, and laypeople, it shows that rather than being peripheral, economic exchanges are often central to the relations between Buddhist monastics and laity, and are a key topic of religious debate. Based on long-term ethnographic fieldwork from India over Russia to Japan, and including all three major Buddhist traditions, the book focuses on the flows of goods and services between clergy and laity, the management of resources, the treatment of cash, and the role of the state in temple economies. Along with documenting ritual and economic practices, these accounts engage with the anxieties and challenges facing Buddhist societies in the contemporary era and dispel the romantic notion of the Buddhist monk"--